2001
DOI: 10.1103/physrevb.63.054510
|View full text |Cite
|
Sign up to set email alerts
|

Critical currents and vortex states at fractional matching fields in superconductors with periodic pinning

Abstract: We study vortex states and dynamics in two-dimensional ͑2D͒ superconductors with periodic pinning at fractional submatching fields using numerical simulations. For square pinning arrays we show that ordered vortex states form at 1/1,1/2, and 1/4 filling fractions while only partially ordered states form at other filling fractions, such as 1/3 and 1/5, in agreement with recent imaging experiments. For triangular pinning arrays we observe matching effects at filling fractions of 1/1, 6/7, 2/3, 1/3, 1/4, 1/6, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
107
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 58 publications
14
107
3
Order By: Relevance
“…In this regime, the vortices act like charged point particles and their interaction with periodic pinning potential can be described using molecular dynamic simulations. 18,19,20,21 . However, the overlap of vortex cores (with size ∼ ξ), and the exact shape of the inter-vortex interaction (depending on the superconducting material properties reflected through κ), may significantly modify the vortex structures and consequently the critical current when this criteria is no longer satisfied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regime, the vortices act like charged point particles and their interaction with periodic pinning potential can be described using molecular dynamic simulations. 18,19,20,21 . However, the overlap of vortex cores (with size ∼ ξ), and the exact shape of the inter-vortex interaction (depending on the superconducting material properties reflected through κ), may significantly modify the vortex structures and consequently the critical current when this criteria is no longer satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, arrays of microholes (antidots) 1,2,3,4,5,6,7,8,9,10,11,12 and submicron magnetic dots, 13,14,15 have been studied, as their presence in the SC film strongly modifies the vortex structure compared to the one in non-patterned films. 16,17 Direct imaging experiments, 1 magnetization and transport measurements, 2,3,4,5 and theoretical simulations 18,19,20,21,22 of vortex structures in samples with periodic pinning centers have shown that the vortices form highly ordered configurations at integer H n = nΦ 0 /S and at some fractional H p/q = p q Φ 0 /S (n,p,q being integers) matching fields, where Φ 0 = hc/2e = 2.07 · 10 −7 Gcm 2 is the flux quantum, and S is the area of the primitive cell of the artificial lattice. This remarkable variety of stabilized vortex lattices may even be broadened by multiple possible degeneracies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7(a) [19]. One might anticipate that a multi-domain state would have lower energy, even exactly at the matching field, since the chain state clearly represents an inefficient way of packing vortices [20]. The multi-domain SHPM image captured at H ¼ ÀH 1 =3 (Fig.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…The typical matching signature is the appearance of minima in the resistivity (or maxima in the critical current) for magnetic fields such that the number of vortices n V is a multiple (or a simple fraction like 1/4, 1/2 and 3/4) of the number of minima n P in potential landscape. For this purpose, films having different types of artificial pinning centers like holes [1,2] magnetic [3,4] or non-magnetic particles [5] in different geometries [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21], have been studied both experimentally and theoretically [22,23,24,25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%